A Review: Synthesis, Recent Application and Future Challenge of SiO2 Nanoparticles in Membrane Technology - Widiyanti, Silvia; Iasha, Yurin Karunia Apsha Albaina; Ashfiya, Putri Sayyida; Khoerunnisa, Fitri; Nurhayati, Mita; Hendrawan, Hendrawan; Sonjaya, Yaya; Aziz, Hafiz Aji (Jurnal Kartika Kimia, 2024)
Membrane processes are well-established methods in real water treatment, renowned for their compact size, exceptional treatment effectiveness, and substantial water permeation capacity. The emergence of nanomaterials has ushered in thrilling prospects and progress in the membrane technology. Silica nanoparticles (NPs SiO2), a high-purity amorphous silica powder, is a white fluffy material characterized by its small particle size, and it brings numerous benefits due to its distinctive attributes. With a large specific surface area, strong surface adsorption, considerable surface energy, high chemical purity, and excellent dispersion, it holds significant value in diverse areas like medicine, physics, chemistry, and biology. NPs-SiO2 can be categorized into hydrophilic and hydrophobic types, which offers difference application in the membrane technology. In this review, NPs-SiO2 contained membranes are specifically discussed. The main goal is to provide critical analysis on recent application of SiO2 in membrane technology. Apart from the introduction and conclusion, this review has three consecutive parts including The synthesis methods of NPs-SiO2 contained membrane including size of the NPs-SiO2 that is mostly used in membranes, the application of the hydrophobic and hydrophilic NPs-SiO2 in the membrane technology, and the future challenge of NPs-SiO2 used in membrane technology.